An analytical multicriteria model based on graph theory for reliability enhancement in distribution electrical networks - Anass Lekbich; Abdelaziz Belfqih; Tayeb Ouaderhman; Jamal Boukherouaa; Faissal El Mariami (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The electrical distribution network is a critical and complex system in terms of safety and reliability, because it is composed of different components (switches, reclosers, etc.). The improvement of its reliability is therefore one of the most important tasks through the good management of remote-controlled switches and reclosers in this network. This paper presents an analytical model based on graph theory to evaluate SAIDI and SAIFI indices based on the network architecture and the location of remote-controlled reclosers and switches. These indicators have been used to formalize a multi-objective mathematical model that respects the real operation constraints of equipments in smart grid. The applied model, in this article, was evaluated on an IEEE 13 bus network using the TOPSIS method to determine the optimal location of the switches and reclosers and to improve the overall reliability of the distribution network.